IgG4‐Related Disease: Clinical and Laboratory Features in One Hundred Twenty‐Five Patients. Issue 9 (September 2015) - Wallace, Zachary S.; Deshpande, Vikram; Mattoo, Hamid; Mahajan, Vinay S.; Kulikova, Maria; Pillai, Shiv; Stone, John H.
<x xml:space="preserve">Abstract</x> Objective IgG4‐related disease (IgG4‐RD) is an immune‐mediated fibroinflammatory condition that can affect nearly any organ. Prior studies have focused on individual cases of IgG4‐RD or small case series. This study was undertaken to report detailed clinical and laboratory findings in a larger group of patients with IgG4‐RD whose diagnosis was established by strict clinicopathologic correlation. Methods The baseline features of 125 patients with biopsy‐proven IgG4‐RD were reviewed. The diagnosis was confirmed by pathologists' review, based on consensus diagnostic criteria and correlation with clinicopathologic features. Disease activity and damage were assessed using the IgG4‐RD Responder Index (RI). Flow cytometry was used to assess levels of circulating plasmablasts. Results Of the 125 patients, 107 had active disease and 86 were not receiving treatment for IgG4‐RD. Only 51% of the patients with active disease had elevated serum IgG4 concentrations. However, patients with active disease and elevated serum IgG4 concentrations were older, had a higher IgG4‐RD RI score, a greater number of organs involved, lower complement levels, higher absolute eosinophil counts, and higher IgE levels compared to those with active disease but normal serum IgG4 concentrations (P < 0.01 for all comparisons). The correlation between IgG4+ plasmablast levels and the IgG4‐RD RI of disease activity (Spearman's ρ = 0.45, P = 0.003) was stronger than the correlation between total plasmablast levels and the IgG4‐RD RI. Seventy‐six (61%) of the patients were male, but no significant differences according to sex were observed with regard to disease severity, organ involvement, or serum IgG4 concentrations. Treatment with glucocorticoids failed to produce sustained remission in 77% of patients. Conclusion Nearly 50% of this patient cohort with biopsy‐proven, clinically active IgG4‐RD had normal serum IgG4 concentrations. Elevations in the serum IgG4 concentration appeared to identify a subset of patients with a more severe disease phenotype. In addition, the levels of IgG4+ plasmablasts correlated well with the extent of disease activity.